THE DEVELOPMENT OF CHILDREN’S CREATIVITY: A SYSTEMATIC LITERATURE REVIEW - Lulu Noorkholisoh (Universitas Pendidikan Indonesia, 2021)
Creativity refers to the individual's ability to think constructively and generate new ideas, the universal characteristic of creativity is the novelty and freshness of ideas. 80% of creativity in children is product-oriented, in other words, creative children are those who are able to create new products or ideas, whether they are really new or things that have existed before but are renewed. The development of children's creativity follows a curved trajectory consisting of peaks and declines. Recent research states that the development of children's creativity has a linear direction of other developments. This article discusses the development of creativity in children using the Systematic Literature Review method to examine 53 articles from five databases, which finally resulted in seven articles that met the criteria to be identified in this study.